SALAFI-WAHABI VS NU (Pertentangan Keberadaan STAI Ali bin Abi Thalib di Semampir Surabaya) - Raudatul Ulum (Harmoni, 2016)
The dispute between the adherents of Salafi-Wahabi and Nahdlatul Ulama often occure in various places in Indonesia. The perspectives of the two groups are different and difficult to collaborate. This is also the case in the sub-district of Semampir – east Java when the people of Kecamatan Semampir – Desa Sidotopo Kidul – East Java rejected violently the establishment of the STAI Ali Bin Abi Thalib – an educational institutions founded by Salafi-Wahabi adherents. This study was conducted to understand the various issues concerning the causes of the conflict and what efforts have been made by the Ministry of Religious Affair to elaborate that dissindents. Through observation techniques and in-depth interviews with the people who involved in the conflict, we conclude that the main problem of the conflict are due to differing opinions about religious understanding and theological concept. The Salafi- Wahabi-affiliated institution criticized the traditions of NU through the publication of newsletter and bulletin, radio broadcasting and Friday sermons. The disagreement of the two parties, Salafi Wahabi and NU, is derived from their missionary endeavor and religious attitudes which are extremely contradictive and difficult to compromise. This study provides recommendations to stakeholders such as Ministry of Religious Affairs – East Java government and other civil society organizations working in the field of religion to continue the discussions, dialogues and other effective communication methods in order to unify and resolve the conflict.